2012
DOI: 10.1258/ult.2012.012014
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of sonographers unaffected by work-related musculoskeletal disorders

Abstract: There is much concern amongst sonographers that reported cases of work-related musculoskeletal disorders (WRMSD) seem to be increasing at an alarming rate. Various studies have been published quoting high incidences within the profession, but there is a dearth of contemporary, robust evidence. Within the profession, anecdotal evidence suggests that a number of sonographers have been practising full-time for a number of years without experiencing any symptoms of WRMSD. In order to explore this phenomenon in mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…This correlates with the study of sonographers who were unaffected by WRMSD, which found that a positive outlook, job satisfaction, control over the workload and equipment selection were commonly referred to by respondents. 11 Workers' attitudes and beliefs can also impact on their risk of WRMSD. 10 Are you the type of person that will go to great lengths to achieve the perfect image, despite aches and pains?…”
Section: Psychosocial Factorsmentioning
confidence: 99%
“…This correlates with the study of sonographers who were unaffected by WRMSD, which found that a positive outlook, job satisfaction, control over the workload and equipment selection were commonly referred to by respondents. 11 Workers' attitudes and beliefs can also impact on their risk of WRMSD. 10 Are you the type of person that will go to great lengths to achieve the perfect image, despite aches and pains?…”
Section: Psychosocial Factorsmentioning
confidence: 99%
“…Gibbs and Edwards 26 have reported a study that identified 22 sonographers who were actively practicing sonography without experiencing symptoms of musculoskeletal discomfort. Their findings indicated that participating sonographers believed that they avoided WRMSDs as a result of postural adjustments, with no special equipment used.…”
Section: General Recommendations For Workplace Improvementsmentioning
confidence: 99%
“…Given the inherent physical risk factors that many radiologic professionals face because of the nature of their job tasks, consistent and intermittent reminders about basic safety principles are important. [26][27][28] Previous research studies on this subject have recommended that radiologic professionals receive a workshop or training session approximately every 6 months in hopes of reinforcing safe scanning techniques and positions. Allowing participants to view a multimedia tutorial that includes pictures and explanations of safe scanning practices at a minimum of 4-to 6-month intervals would likely be beneficial.…”
Section: Practice Education and Research Implicationsmentioning
confidence: 99%
“…Work-related musculoskeletal disorders (WRMSD) are aggravated or caused by workplace activities. According to the U.S. Department of Labor, Occupational Safety and Health Administration, 1 risk factors for WRMSD include (1) prolonged static positions, (2) awkward body postures, (3) forceful exertions, (4) repetitive movements, and (5) vibrations. With the exception of vibrations, sonographers routinely engage in all of the remaining risk factors.…”
mentioning
confidence: 99%
“…2,3 Of these, poor posture and repetitive movements have been reported as primary causes of WRMSD in sonographers, [4][5][6] while other variables such as age, experience level, and exam types do not appear to affect WRMSD risk. 4,5,[7][8][9] Work-related musculoskeletal injuries are very common among sonographers. 3 The first report of WRMSD, known as sonographer's shoulder, was introduced by Craig.…”
mentioning
confidence: 99%